Pregnant Women and Opioid Use Disorder: Examining the Legal Landscape for Controlling Women's Reproductive Health. Issue 2 (July 2022) - Madden, Lynn M.; Oliva, Jenn; Eller, Anthony; DiDomizio, Elizabeth; Roosa, Mat; Blanchard, Lisa; Kil, Natalie; Altice, Frederick L.; Johnson, Kimberly
Abstract: Women with opioid use disorder ("OUD") are more likely than other women to experience sexual assault, unintentional pregnancy, transactional sex and coercion regarding reproductive health care choices than women without OUD. Laws described as family friendly may be punitive rather than helpful to women and rarely apply to men. Laws regarding reproductive health and OUD are unevenly enforced and therefore biased against poor, minority women. As part of a larger study oriented toward strengthening systems of care related to the intersection of HIV and OUD, we conducted an analysis of state laws related to pregnant and postpartum women with OUD. Data on disparities in child removals and pregnant women's use of evidence-based treatment for OUD by income and race were captured for the five states with the most restrictive laws in both categories. Laws that were purportedly designed to improve reproductive health outcomes for women with OUD and/or their children often have the opposite of the expressed intended outcome. There is a relationship between restrictive reproductive choice and coercive OUD treatment policy for women. Restrictive state regulations for pregnant women with OUD persist despite negative outcomes for maternal and child health. Altering coercive and/or criminalizing regulation and redefining 'family friendly' may improve outcomes for individuals and families.